Difference in Acquired Radioresistance Induction Between Repeated Photon and Particle Irradiation - Sato, Katsutoshi; Shimokawa, Takashi; Imai, Takashi (Frontiers in Oncology, 2019)
In recent years, advanced radiation therapy techniques, including stereotactic body radiotherapy and carbon‑ion radiotherapy, have progressed to such an extent that certain types of cancer can be treated with radiotherapy alone. The therapeutic outcomes are particularly promising for early-stage lung cancer, with results that match those of surgical resection. Nevertheless, patients may still experience local tumor recurrence, which might be exacerbated by the acquisition of radioresistance after primary radiotherapy. Notwithstanding the risk of tumors acquiring radioresistance, secondary radiotherapy is used increasingly to treat recurrent tumors. In this context, it appears essential to comprehend the radiobiological effects of repeated photon and particle irradiation and their underlying cellular and molecular mechanisms to achieve the most favorable therapeutic outcome. However, to date, the mechanisms of acquisition of radioresistance in cancer cells have mainly been studied after repeated in vitro X-ray irradiation. In contrast, other critical aspects of radioresistance remain mostly unexplored, including the response to carbon‑ion irradiation of X-ray radioresistant cancer cells, the mechanisms of acquisition of carbon‑ion resistance, and the consequences of repeated in vivo X-ray or carbon‑ion irradiation. In this review, we discuss the underlying mechanisms of acquisition of X-ray and carbon‑ion resistance in cancer cells, as well as the phenotypic differences between X-ray and carbon‑ion resistant cancer cells, the biological implications of repeated in vivo X-ray or carbon‑ion irradiation, and the main open questions in the field.